“It Makes us Realize that We Have Been Heard”: Experiences with Open Dialogue in Vermont - Florence, Ana Carolina; Jordan, Gerald; Yasui, Silvio [UNESP]; Cabrini, Daniela Ravelli [UNESP]; Davidson, Larry (Springer Nature, 2021)
The Open Dialogue approach was developed in Finland as a form of psychotherapy and a way to organize mental health systems. Open Dialogue has drawn global interest leading to adaptations worldwide, including in Vermont-US where it is called Collaborative Network Approach. Our study aimed to investigate the experiences of families who received Collaborative Network Approach in two agencies in Vermont. Qualitative interviews were conducted with 17 persons receiving services. Seven themes emerged: 1) network focus, 2) decision-making, 3) structure of care, 4) use of reflections, 5) medications, 6) hospitalizations, 7) challenges. Our study provides evidence that CNA is well-received, appreciated, and for many people an empowering form of mental health care. The findings suggest that elements of Open Dialogue are highly consistent with the vision for recovery-oriented care, in that they are flexible, person-centered, encourage processes of negotiation, and highlight the importance of family and social supports in care.
Keywords: Families; Mental health and illness; Open dialogue; Psychosis; Recovery; Users’ experiences